(untitled) (diségno, 2024)
A landscape is always the result of the sum, on the one hand of natural and anthropic transformations and, on the other, of the readings and interpretations attributed to it: this is why its representation constantly oscillates between the ‘inside’ and the ‘outside’ of reality, or rather, between reality and imaginary. If each of these factors, objective and subjective, informs and enriches space with a different temporal imprint, each landscape presents itself as a diachronic record of several landscapes that have succeeded one another over time. Faced with ancient landscapes marked by the condition of palimpsest, it is necessary to implement techniques and methods for representation to express both the character of stratification they embody and the dual nature, objective and subjective, that characterizes their description. Through a graphic exercise in two ‘acts’, this contribution intends to apply this tension to the landscape long referred to as the ‘Roman countryside’, a topos in iconographic representation since the 17th century. The territory of the outskirts of Rome provides a model for the investigation of landscapes similarly connoted by the condition of the palimpsest, demonstrating how drawing, thanks to its inherent operation of synthesis, constitutes a powerful tool for analyzing and describing the transformation of space through the phases that have overlapped and erased in it, giving tangible form to what most intangible exists: time.